Dietary Macronutrients Do Not Differently Influence Postprandial Serum and Plasma Brain-Derived Neurotrophic Factor Concentrations: A Randomized, Double-Blind, Controlled Cross-Over Trial - Gravesteijn, Elske; Mensink, Ronald P.; Smeets, Ellen T. H. C.; Plat, Jogchum (Frontiers in Neuroscience, 2021)
Objectives: Brain-derived neurotrophic factor (BDNF) plays a role in cognition and metabolism. Specific nutrients can affect fasting BDNF concentrations, which are potentially mediated by insulin and/or glucose. Since macronutrients trigger each a different insulin and glucose response, we examined postprandial effects of meals rich in fat, carbohydrates, or protein on BDNF concentrations. BDNF was analyzed in serum and plasma, since concentration differences can be found between matrices. Methods: Healthy overweight/obese male participants (n = 18) participated in this randomized, double-blind, cross-over trial consisting of three test days with 1 week wash-out periods. Either a high-fat (En% fat, carbohydrates, protein: 52.3, 39.2, 8.0), high-carbohydrate (En% 9.6, 81.5, 8.6) or high-protein meal (En% 10.6, 51.5, 36.9) was consumed on each test day. BDNF concentrations were measured after 0, 60, and 240 min. Glucose and insulin concentrations were measured after 0, 15, 30, 45, 60, 90, 120, and 240 min. Results: BDNF concentrations were higher in serum compared with plasma (P < 0.001). Postprandial BDNF concentrations in serum decreased significantly after the high-fat (P = 0.013) and high-carbohydrate meals (P = 0.040), and showed a trend after the high-protein meal (P = 0.076). No differences were found between meals (P = 0.66). Postprandial BDNF concentrations measured in plasma did not significantly change after the different meals (P = 0.47). As total area under the curve (AUC) for glucose was significantly higher after the high-carbohydrate meal compared with the high-fat (P = 0.003) and high-protein meals (P < 0.001), and the total AUC for insulin was higher after the high-carbohydrate (P < 0.001) and high-protein meals (P < 0.001) compared with the high-fat meal, it seems that acute changes in glucose and insulin do not affect postprandial BDNF concentrations. However, after the high-protein meal, the higher total AUC for glucose correlated with lower serum BDNF concentrations, and a higher maximal increase in glucose correlated with a lower maximal increase in plasma BDNF concentrations. There were no correlations with insulin concentrations after either meal. Conclusion: Serum BDNF concentrations were higher than plasma concentrations. Since postprandial BDNF responses were not different between the meals, we conclude that there is no role for insulin or glucose in regulating postprandial BDNF concentrations. Clinical Trial Registration: [www.ClinicalTrials.gov], identifier [NCT03139890].